Peer-to-Peer lending platform: From substitution to complementary for rural banks - Cliff Kohardinata; Novrys Suhardianto; Bambang Tjahjadi (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
This study aims to examine the impact of the growth of peer-to-peer (P2P) lending on the growth of rural bank lending. Further, this study investigates the outcome of the partnership agreement between the Rural Bank Association and Financial Technology (FinTech) Association in the last quarter of 2017 on the effect of P2P lending on rural bank lending by analyzing the impact separately in 2018 and 2019. The publicly available data from the Financial Services Authority and Bank of Indonesia were examined using panel data regression. The results show that P2P lending's growth is a substitute for the growth of the rural bank loan in 2018. However, the partnership between the Rural Bank Association and FinTech Association changed the effect of substitution into complementary in 2019. Moreover, the impact of P2P lending was more prominent in provinces with a higher number of rural banks and regions with lower economic growth. The restricted number of publicly available data becomes the limitation of this study to obtain the best results.
Keywords: G21; G23; O33; 650; banking; rural bank; FinTech; P2P lending; substitution; complementary